The Effect of Single Garlic Extract (Allium Sativum Var. Solo Garlic) Administration on Weight Gain in Male Rattus Wistar Rats with Dyslipidemia - Miranda Winda Sari Sitorus; Suandy, Suandy; Linda Chiuman (Yayasan Literasi Sains Indonesia, 2025)
Background: Dyslipidemia is an abnormal condition (increase or decrease) in cholesterol lipoproteins, including an increase in total cholesterol, triglycerides, and low-density lipoprotein (LDL) levels, as well as a decrease in high-density lipoprotein (HDL) levels. Metabolism plays a role in converting nutrients into compounds necessary for life processes, such as energy sources (ATP). Research Objective: To determine the effect of administering single garlic extract (Allium sativum var solo garlic) on weight gain in male Rattus winstar rats with dyslipidemia. Research Methods: This quasi-experimental study used 24 male Wistar rats, single garlic extract, butter, quail eggs, used cooking oil, and scales. The study population consisted of 24 male Wistar rats, which were divided into four groups of six rats each using Federer's formula. The treatments in this study were: the positive group was given standard feed and simvastatin; the negative group was given standard feed and aquabides; treatment group 1 was given 200 mg/kgBW of single garlic extract; and treatment group 2 was given 400 mg/kgBW of single garlic extract. Body weight assessments were conducted four times, namely on days 7, 14, 21, and 28. The research data analyzed were total cholesterol, LDL count, HDL count, triglyceride count, and body weight. Data were analyzed for normality using the Shapiro-Wilk test, and if normally distributed, continued with a one-way parametric ANOVA test and Tukey HSD post-hoc test. Data were analyzed using IBM SPSS 23 for Windows, with P values < 0.05 interpreted as statistically significant. Research Results: The mean values and standard deviations for the positive group were 234±13.20 on day 7, 223±12.29 on day 14, 231.83±11.99 on day 21, and 227.5±10.15 on day 28. Negative group on day 7 (237.33±18.52), day 14 (240±7.84), day 21 (238.5±17.28) and day 28 (239.16±9.62). Treatment 1 on day 7 (261.5±27.22), day 14 (296±21.63), day 21 (316.33±21.05) and day 28 (334.16±17.03). Treatment 2 on day 7 (290±10.62), day 14 (327.16±7.41), day 21 (344.33±45.39) and day 28 (385.83±13.43). Administration of 400 mg/kgBW single garlic extract significantly (P = 0.02 < 0.05) increased the body weight of rats compared to the positive and negative control groups. Conclusion: Based on the results of this study, single garlic extract in test animals showed an increase in body weight in dyslipidemic rats, indicating the need for further research on the mechanism of weight gain due to the administration of single garlic extract.